Comparative Study of Oyster Mushroom and Oyster Mushroom Income Corn Cob Mushroom in Mataram City - Suardana, I Wayan Agus; Herdiana, Herdiana; Mappanganro, Nurlailah (Implikasi: Jurnal Manajemen Sumber Daya Manusia, 2023)
This research aims to analyze the differences in farming oyster mushrooms and corncob mushrooms, how much the comparison of income affects the income level of oyster mushroom and corncob mushroom farmers in the city of Mataram and to find out the obstacles in farming oyster mushrooms and corncob mushrooms. Determining the location in this research was carried out using purposive sampling, meaning that sampling was carried out deliberately. The research location is in Mataram City, namely in six sub-districts, namely Mataram District, Ampenan District, Sekarbela District, Selaparang District, Cakranegara District, and Sandubaya District. Determining respondents was carried out using the census method, namely taking respondents as a whole. The respondents in this research were oyster mushroom and corncob mushroom farmers spread across six sub-districts. The research results show: firstly, the average production of oyster mushrooms is 1,650 kilograms per 100 m2 per year, which is greater than the average production of corn weevil mushrooms of 830 kilograms per 100 m2. The average production cost of oyster mushroom farming is IDR. 11,533,100,- per 100 m2 per year, which is greater than the average production cost of corn weevil mushrooms, which is Rp. 10,434,641,- per 100 m2 per year. Second, the average income in oyster mushroom farming is IDR. 21,466,900,- per 100 m2 per year, greater than the income from corn weevil mushroom farming, namely Rp. 18,615,359,-per 100 m2, meaning that the income from oyster mushroom farming is greater than the income from corn cob mushroom farming for 1 year. Third, the obstacles faced in carrying out oyster mushroom farming and corn cob mushroom farming are the same as experiencing difficulties in obtaining raw materials, having little capital, limited land, and cheap labor that is difficult to obtain in urban areas